Stability Analysis for Differential Equations of the General Conformable Type. (14th April 2022) - Ben Makhlouf, Abdellatif; El-Hady, El-Sayed; Boulaaras, Salah; Hammami, Mohamed Ali
Abstract : Fractional calculus is nowadays an efficient tool in modelling many interesting nonlinear phenomena. This study investigates, in a novel way, the Ulam–Hyers (HU) and Ulam–Hyers–Rassias (HUR) stability of differential equations with general conformable derivative (GCD). In our analysis, we employ some version of Banach fixed-point theory (FPT). In this way, we generalize several earlier interesting results. Two examples are given at the end to illustrate our results.